(untitled) (Indian Journal of Arid Horticulture, 2025)
Jamun (Syzygium cuminii Skeels) is an important fruit crop belonging to the family Myrtaceae. It is indigenous to India, Burma, and the Andaman Islands (Zeven and de Wet, 1982) and is available throughout the Indian plains, as well as in the Kumaon hills up to an altitude of 1,600 meters (Mishra et al., 2015). The fruits are used as an effective remedy for diabetes, heart disease, and liver disorders. Due to its multiple uses, jamun has emerged as a promising fruit crop in India (Singh et al., 2016). In Gujarat, jamun is commercially cultivated in the districts of Vadodara, Anand, Navsari, Kheda, and Junagadh. Most plantations in these areas consist of seedling-raised trees. However, farmers are increasingly adopting grafted planting material of the Goma Priyanka variety developed by the station.Jamun trees, whether seedling-raised or grafted, exhibit an erect growth habit, reaching heights of 25–30 meters, making harvesting and orchard management challenging. In the absence of proper canopy management, orchards become overcrowded, limiting access and reducing light penetration required for optimal photosynthesis, flowering, fruit set, and quality (Mishra and Goswami, 2016).Pruning has been employed as a technique to regulate tree size and shape, achieving a desirable canopy architecture while reducing foliage density by removing unproductive branches. To maintain a dwarf framework, the topping of the main stem at 4–6 meters is recommended, which facilitates easy harvesting. Studies have shown that pruning 50% of the annual extension growth after harvesting effectively reduces canopy size and improves fruit quality attributes (Singh et al., 2011).Pruning, when performed correctly, shapes the plant to optimize marketable yield. In Konkan Bahadoli jamun, different pruning intensities significantly increased marketable yield (Lawande et al., 2014). The fruit-bearing branches in jamun are distributed throughout the canopy, and fruits do not ripen uniformly. As a result, at least 3–4 pickings are required to harvest fully ripened fruits.Jamun fruits are delicate, with a thin peel, making hand-picking the only viable harvesting method. However, due to the tall nature of the tree, manual harvesting becomes labor-intensive, with 25–30% of fruits suffering mechanical damage. Being a non-climacteric fruit, jamun must be harvested fully ripe to ensure optimal quality. Therefore, managing tree canopy height through pruning is essential for efficient harvesting and maintaining fruit quality. Despite its advantages, pruning in jamun has not been widely adopted as a standard orchard management practice. In this study, different pruning intensities were imposed on mature bearing trees of Goma Priyanka to evaluate their effects on fruit yield and quality.